2001
DOI: 10.1093/oxfordjournals.molbev.a003851
|View full text |Cite
|
Sign up to set email alerts
|

A General Empirical Model of Protein Evolution Derived from Multiple Protein Families Using a Maximum-Likelihood Approach

Abstract: Phylogenetic inference from amino acid sequence data uses mainly empirical models of amino acid replacement and is therefore dependent on those models. Two of the more widely used models, the Dayhoff and JTT models, are estimated using similar methods that can utilize large numbers of sequences from many unrelated protein families but are somewhat unsatisfactory because they rely on assumptions that may lead to systematic error and discard a large amount of the information within the sequences. The alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
2,055
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 2,602 publications
(2,061 citation statements)
references
References 14 publications
4
2,055
0
2
Order By: Relevance
“…In each case, the LG matrix [44] was chosen over the JTT [36] and WAG [37] matrices used in the original analysis by both the AIC and BIC criteria (see Table S1). We nonetheless performed our analyses with all three matrices in order to compare our results to those of Boyer et al [18].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In each case, the LG matrix [44] was chosen over the JTT [36] and WAG [37] matrices used in the original analysis by both the AIC and BIC criteria (see Table S1). We nonetheless performed our analyses with all three matrices in order to compare our results to those of Boyer et al [18].…”
Section: Methodsmentioning
confidence: 99%
“…The analyses of Boyer et al [18] used traditional evolutionary models (JTT [36] and WAG [37]) of the type that can be sensitive to LBA and/or compositional heterogeneity [22], [32]. Moreover, previous analyses of deep phylogeny have revealed that substantial differences in evolutionary rates and composition affect molecular sequences sampled from the three cellular domains [15].…”
Section: Introductionmentioning
confidence: 99%
“…PROTTEST tests for 72 amino acid substitution models. The best substitution matrix suggested by PROTTEST, the WAG matrix (Whelan and Goldman 2001), was used for ML analyses, using PHYML (Guindon and Gascuel 2003). The ML analysis was used to correct the consensus tree considering a 0.016 fraction of the total sites as invariant and used a gamma distribution with a = 0.908 as obtained from PROTTEST.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…Bayesian analysis was performed using MrBayes v3.1.2 (Ronquist and Huelsenbeck 2003). Default priors and the WAG model (Whelan and Goldman 2001) were used assuming equal rates across sites. Two independent analyses were run with three heated and one cold chains (temperature parameter 0.2) for 3 × 10 6 generations, with a sampling frequency of 0.01 and the first 25 % of the generations were discarded as burn-in.…”
Section: Phylogenetic Analysismentioning
confidence: 99%